2022
DOI: 10.1007/s10750-022-04912-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Post-Tropical Storm Arthur (2014) on benthic Arcellinida assemblage dynamics in Harvey Lake, New Brunswick, Canada

Abstract: Arcellinida (testate lobose amoebae) were examined in surface-sediment samples collected in 2015 from throughout Harvey Lake, New Brunswick, Canada to assess whether the passage of Post-Tropical Storm Arthur in 2014 impacted the distribution of taxa and assemblages. Cluster analysis and non-metric multidimensional scaling (NMDS) revealed four distinct arcellinidan assemblages. Redundancy Analysis (RDA) and partial-RDA results were used to identify four variables that significantly influenced the assemblage com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…MA1 is characterised by a high occurrence of elongated, spiky and flattened shells, which is typical for shallow water assemblages (Atasiei et al., 2022; Golemansky, 2007; Golemansky, 2008; Dabés & Velho, 2001; Schönborn, 1961, 1989). The observed predominance of elongate shells at the studied sites is the result of adaptation to living in ecotopes with a plenty of macrophytes (Arrieira et al., 2015; Lansac‐Tôha et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MA1 is characterised by a high occurrence of elongated, spiky and flattened shells, which is typical for shallow water assemblages (Atasiei et al., 2022; Golemansky, 2007; Golemansky, 2008; Dabés & Velho, 2001; Schönborn, 1961, 1989). The observed predominance of elongate shells at the studied sites is the result of adaptation to living in ecotopes with a plenty of macrophytes (Arrieira et al., 2015; Lansac‐Tôha et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Core HL‐2017‐GC‐3, collected from open water in the central part of the lake, was characterized by a series of relatively old radiocarbon dates with a basal radiocarbon date of ∼6,600 Cal BP at 180–184 mm core depth, indicating a very low sediment accumulation rate of >70 years per 2 mm. As Harvey Lake is not stratified, with the lake bottom being well oxygenated at all depths (Atasiei et al., 2022; Patterson et al., 2020) it is likely that deposition of organic and inorganic sediments in the central part of the lake is being impacted by factors such as productivity, oxygen exposure time, and the activities of microbial decomposers (Sobek et al., 2009). At the sampling resolution possible using a Glew core extruder (2 mm), it was determined that it would be difficult to reliably discriminate individual paleo‐storm events in such a low sedimentation rate environment so further analysis of this core was suspended.…”
Section: Methodsmentioning
confidence: 99%
“…An assessment of Arcellinida (testate lobose amebae) obtained from sediment‐water interface samples from throughout the Harvey Lake basin in 2015 indicated that Post‐Tropical Storm Arthur also had a significant ecological impact. It was determined that the deepening of the wave base during the passage of the storm resulted in arcellinidans, a key intermediary trophic food web component, being carried into suspension along with very coarse silt grain particles and then redeposited at all water depths throughout the lake, forming exotic species assemblages (Atasiei et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…What makes some species of Arcellinid more resistant than others is still a mystery. However, Arcellinids are currently used as bioindicators and in monitoring freshwater environments (ARRIEIRA et al, 2015;ATASIEI et al, 2022;NASSER et al, 2020;PATTERSON;SWINDLES, 2010). Their main advantages as a study model are that they are easy to find and have low-cost work.…”
Section: Testate Amoebae As Models For Studies Of Environmental Impactmentioning
confidence: 99%